An Analysis of Popular Fiction Movie: Feminism in Movie Miss Peregrine’s Home for Peculiar Children (2016) - Riris Yusrina (Universitas Gadjah Mada, 2022)
Film is one of American popular culture that attracts many people around the world. America has many movie genres, one of which is a fictional film genre. Fiction works do have very unique characters, from the storyline to the characters in the fictional film. In addition, in the modern era, feminism has been applied in everyday life, starting from education, politics, etc. This article analyzed the feminism of the character of Miss Peregrine in the American fiction film titled Miss Peregrine's Home for Peculiar Children (2016) by using semiotic theory. The results show that several scenes in the film represent feminism through Miss Peregrine's character, those are as a hero and as a leader. In addition, there is ecofeminism in the film.